2011
DOI: 10.1111/j.1365-3059.2011.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection ofFusariumpathogens and their mycotoxins in South African maize

Abstract: The distribution and co-occurrence of four Fusarium species and their mycotoxins were investigated in maize samples from two susceptible cultivars collected at 14 localities in South Africa during 2008 and 2009. Real-time PCR was used to quantify the respective Fusarium species in maize grain, and mycotoxins were quantified by multi-toxin analysis using HPLC-MS. In 2008, F. graminearum was the predominant species associated with maize ear rot in the eastern Free State, Mpumalanga and KwaZulu-Natal provinces, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 39 publications
(45 reference statements)
5
55
1
Order By: Relevance
“…We observed a similar trend in China, where the ratio of F. subglutinans to F. proliferatum proved highest in Heilongjiang and Jilin in the most northern and coldest region in China, while in the more southern provinces Gansu and Hebei, no F. subglutinans was isolated. These results support the notice that F. subglutinans prefers a cooler temperature (Boutigny et al, 2012;Goertz et al, 2010;Logrieco et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…We observed a similar trend in China, where the ratio of F. subglutinans to F. proliferatum proved highest in Heilongjiang and Jilin in the most northern and coldest region in China, while in the more southern provinces Gansu and Hebei, no F. subglutinans was isolated. These results support the notice that F. subglutinans prefers a cooler temperature (Boutigny et al, 2012;Goertz et al, 2010;Logrieco et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…Quantification of F. verticillioides, F. proliferatum and F. subglutinans using Real Time PCR The primers used for the detection of F. subglutinans were Fsub565 F (TCATTGGTATGTTGTCGCTCATG) and Fsub622A R (GTGATATGTTAGTACGAATAAAGGGAGAAC), designed on the EF1g ene (Nicolaisen et al, 2009;Boutigny et al, 2012). The primers Fp3-F (CGGCCACCAGAGGATGTG) and Fp4-R (CAACACGAATCGCT TCCTGAC), designed by Jurado et al (2006) on the intergenic sequence of the ribosomal RNA gene cluster, for the detection of F. proliferatum and the primers VER1 and VER2, designed by Mulè et al, 2004 on the calmodulin gene, for the detection of F. verticilliodes, were used in Real Time as described by Nutz et al (2011); all were synthesized by PRIMM (PRIMM srl, Milan, Italy).…”
Section: Preliminary Species-specific Pcrmentioning
confidence: 99%
“…To assess the presence of inhibitors in maize, the method described by Boutigny et al (2012) was followed. qPCR reactions were performed in a MyiQ TM 2 Two-Colour Real-Time PCR detection system (Bio-Rad, Hercules, USA) with a 96-well reaction plate and Tungstenhalogen optical lamp.…”
Section: Target Dna Quantificationmentioning
confidence: 99%
“…These authors also reported a number of samples from Mokopane (Limpopo) and Lusikisiki (Eastern Cape) containing excessive fumonisin levels. Boutigny et al (2012) reported that F. verticillioides was the predominant fungus in maize at 14 commercial localities in the North-West, the western Free-State and Northern Cape provinces, while F. proliferatum was not detected at any of the localities.…”
mentioning
confidence: 95%